Catalog of Publications 1997-1998 - International Service for National Agricultural Research (International Service for National Agricultural Research, 1997)
The 1997–98 ISNAR Catalog of Publications lists all official ISNAR publications currently in print, as well as several books produced in collaboration with other publishers.